2021
DOI: 10.1039/d1sc03631a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationships in aryl diazirines reveal optimal design features to maximize C–H insertion

Abstract: Diazirine reagents allow for the ready generation of carbenes upon photochemical, thermal, or electrical stimulation. Because carbenes formed in this way can undergo rapid insertion into any nearby C–H, O–H...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 72 publications
1
48
0
Order By: Relevance
“…15 By contrast, bis-(aryl) ether 3 afforded 54% yield of crosslinked cyclohexane, while the most electron-rich bis-diazirine, 9, gave a 91% yield of the desired adduct. Based upon prior studies from Sheridan and Raimer, 24,25 as well as our recent Hammett experiments with mono-diazirines, 22 we attribute the >10-fold increase in crosslinking efficiency for 9 vs. 1 to the different degrees of stabilization of the singlet carbene that is generated following diazirine activation. Significantly, despite the use of a flexible, non-fluorinated tether, we observed no cyclization products forming from compound 9.…”
Section: Benchmarking Of Crosslinker Performancementioning
confidence: 78%
See 1 more Smart Citation
“…15 By contrast, bis-(aryl) ether 3 afforded 54% yield of crosslinked cyclohexane, while the most electron-rich bis-diazirine, 9, gave a 91% yield of the desired adduct. Based upon prior studies from Sheridan and Raimer, 24,25 as well as our recent Hammett experiments with mono-diazirines, 22 we attribute the >10-fold increase in crosslinking efficiency for 9 vs. 1 to the different degrees of stabilization of the singlet carbene that is generated following diazirine activation. Significantly, despite the use of a flexible, non-fluorinated tether, we observed no cyclization products forming from compound 9.…”
Section: Benchmarking Of Crosslinker Performancementioning
confidence: 78%
“…As part of a comprehensive structure-function survey of aryl diazirines, we recently examined the effect of aryl group electronics on spectral properties, activation energy, activation temperature, singlet-triplet carbene gap, C-H insertion barriers, and efficiency of insertion into an aliphatic substrate. 22 We found that electron-poor and electron-neutral trifluoromethyl aryl diazirines were relatively inefficient at reacting with unactivated C-H bonds, regardless of whether thermal or photochemical excitation was used to generate the reactive carbene intermediate. By contrast, the addition of a paraalkoxy group to the aryl diazirine motif conferred a number of important advantages: the UV/Vis absorbance spectrum was shifted to longer wavelengths, the activation temperature was lowered, and-most significantly-the efficiency of C-H insertion to a model aliphatic substrate was improved by up to an order of magnitude.…”
Section: Introductionmentioning
confidence: 87%
“…The use of diazirine-based molecules as cross-linkers of aliphatic polymer materials was previously reported by our group. 43 , 44 Chemical approaches based on the formation of covalent bonds between a photosensitizer and the surface can increase the stability of the material. 39 Additionally, since the porphyrin is covalently attached to a surface, the molecule is prevented from leaching into the environment, meaning that bioaccumulation will not be a concern and it will not be necessary to develop a method for the removal of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore oxygen is a major quencher of photogenerated carbene radicals while the much slower oxidation of nitrene only moderately reduces the C−H insertion rates, reported as the “reciprocity failure” in conventional photoresists [11b] . One possible solution to the air‐sensitivity of phenyl carbene‐based crosslinkers is to switch their ground state to singlet (unreactive to 3 O 2 ) by substitution of the aromatic ring, as predicted by Wulff and co‐workers [16b] . It is also important to note recent studies on the patterning of functional polymers with carbene‐based crosslinkers did not specify the required atmosphere for patterning [13a,b] …”
Section: Resultsmentioning
confidence: 97%